Does CEO turnover matter in China? Evidence from the stock market - Pierre Pessarossi; Laurent Weill (Bank of Finland, Institute for Economies in Transition (BOFIT), 2012)
We study the consequences of CEO turnover announcements on the stock prices of firms in China, where most listed firms remain majority-owned by the state. Our proposition is that state ownership may affect stock market reaction to CEO replacement because state-owned firms often pursue multiple, potentially contradictory, objectives, i.e. economic performance and social objectives. Applying standard event study methodology to a sample of 1,094 announcements from 2002 to 2010, we find that CEO turnover typically produces a positive stock market reaction. The reaction is significantly positive, however, only for enterprises owned by the central government, and not significant for enterprises owned by local governments or privately owned enterprises. These results suggest that a CEO turnover in a central state-owned enterprise signals a renewed commitment to the economic performance objective by state officials. The small size of CEO labor market suggests that other shareholders have a relatively small pool of CEO talent to proceed to managerial improvement when a CEO turnover takes place.
URN:NBN:fi:bof-201408071984
Keywords: G30; M51; P34; O16; 330; CEO turnover; corporate governance; state ownership; China; event study